Literature Review: Tren Pembelajaran Berbasis Augmented Reality (AR) Berdasarkan Analisis Bibliometrik Menggunakan Dimensions AI - Syahrial A; Yulia Hasan; Muhammad Taufik; Hikmawati Hikmawati (Lembaga Bale Literasi, 2025)
This study aims to analyze trends in Augmented Reality (AR) based learning research using bibliometric analysis through Dimensions AI for the period 2016–2025. The method used is descriptive quantitative, analyzing the number of publications, research fields, authors, and publication types. The results show a significant increase in AR publications since 2016, peaking in 2023. The most dominant publication type is scientific articles (43,446 publications), with Education and Curriculum and Pedagogy as the main categories. Several Indonesian researchers are also actively contributing to AR research at the global level. In conclusion, AR research in education is growing rapidly and is interdisciplinary, with development trending toward integrating AR with Artificial Intelligence (AI), Virtual Reality (VR), and Mixed Reality (MR) to create more immersive and adaptive learning.